Association of bone fracture type and degree of callus formation with leptin concentration in children with long bone fractures - Paunović, Zoran; Stanojević, Ivan; Abazović, Džihan; Rakić, Mia; Stanković, Nikola; Djukić, Mirjana; Milutinović, Sanja Milutinović; Starčević, Srdjan; Šupić, Gordana; Vojvodić, Danilo; Jović, Milena; Marić, Dušan (Vojnosanitetski pregled, 2021)
Background/Aim. Recent studies indicate that adipokines have an important role in bone physiology and pathology. Recent data indicate that adipokine leptin functions as a regulator of bone growth at multiple levels, systemically and locally. So far, it has been shown that leptin influences bone volume and bone mineral density in a population with metabolic and/or hormonal abnormality. Data concerning leptin values in non-obese children with fractures are scarce. Methods. This study included 93 non-obese children with long bone fractures (LBF), 14 children with short bone fractures (SBF), and 19 healthy children. Leptin concentration was determined in two blood samples (day 0 and day 21) and analyzed according to gender, fracture type, anatomical localization of the fracture, fracture topography, callus formation, and the healing outcome. Results. Children with LBF demonstrated significantly increased leptin levels compared to the control group (both day 0/day 21). In the control group, girls had significantly more leptin than boys. Leptin value was significantly influenced by anatomical localization since boys and girls with humerus fracture and girls with femur fracture had the highest average leptin concentration in the initial sample. Boys with incomplete callus formation had the highest leptin concentration (both day 0 /day 21), significantly elevated compared to boys’ samples in the control group, boys’ samples with an intermediary and well-formed callus, and also increased compared to the initial samples of girls with incomplete callus. Better callus formation in girls was associated with an increment of leptin concentrations in the second over the initial sample. Girls with partially and satisfactorily formed callus had significantly increased leptin concentration in the second sample (day 21) compared to the boys’ group. Conclusion. Leptin concentration was significantly increased (both samples) in children with LBF compared to children with SBF and corresponding controls. Leptin concentration was highly influenced by gender. High blood leptin concentrations in boys or low leptin concentrations in girls immediately upon fracture could be used to identify groups of children with incomplete callus formation.